PENDAMPINGAN PENGGUNAAN MAINAN WIPE AND CLEAN DAN VIDEO SEBAGAI MEDIA EDUKASI UNTUK MENINGKATKAN PENGETAHUAN PASIEN ANAK TENTANG CARA MENYIKAT GIGI YANG BAIK DAN BENAR - Andina Muzayyanti (Kalam Nusantara Institute, 2023)
The use of effective educational media is essential in improving knowledge acquisition, especially among young patients. This community engagement project aims to support the implementation of educational tools, specifically